UPAYA DINAS KOPERASI PERINDUSTRIAN DAN PERDAGANGAN (KOPERINDAG) KABUPATEN SOLOK DALAM PEMULIHAN PEREKONOMIAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) YANG TERDAMPAK PANDEMI COVID-19 - Rahayu, Suci Rahmat; Khaidir, Afriva (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The, purpose, of this, research, is the efforts of the industry and trade cooperative service (Koperindag) of Solok Regency in the economic recovery of microl, small, and, medium, enterprises, (MSMEs), affected, by the, covid-19, pandemic in order to create MSMEs that are able to survive and become economic drivers, especially after, the, economic, crisis. Therefore, the support of all parties related to government policies is needed. This, research, is a descriptive, analysis, using, a qualitative, approach, that uses primary, data and, secondary, data. The, informants, in this study, were determined, by the, purposive sampling, method, where, the selection, of informants, was based on certain characteristics. Data, collection, techniques, in the, form of field research by interviewing, observing and studying documentation with valid and accurate sources. The, technique tests the validity, of the, data by, triangulation, of methods and source triangulation. While this data analysis technique uses analysis through, the stages, of data deception, data analysis, data reduction and, drawing, conclusions. The results, of this, study, indicate that: First, the efforts made consist of indicators, namely; (1) Creating job opportunities; (2) Reduce unemployment; (3) Reduce poverty; and (4) provide products. Second, internal factors that are owned consist of indicators, namely; (1) Lack of business capital; (2) Limited human resources; (3) Weak network and market penetration capabilities. Third, the external factors that are owned consist of indicators, namely; (1) The business climate is not yet fully condusive, (2) Limited facilities and infrastructure; (3) The impact of regional autonomy; (4) The impact of free markets; (5) Limited market access; (6) Financial limitations.